สิทธิของเหยื่ออาชญากรรมในผลประโยชน์จากการเปิดเผยข้อเท็จจริงในการกระทำ - กานต์ ดุลยฤทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Nowadays, when a sensational crime was committed, the public are always interested in following up to those wrongdoing fact. Hence, offender can expect to receive large sums of money once he is captured by contracting with authors or publishers for selling his story. But there are no any specific provisions under Thai law which can protect victim s right in the profit arisen from disclosure of wrongdoing fact. To be entitled to the profit from crimes, victim must institute an action under tort provision in civil court and recover a judgment for damages. However, there are still some faults and problems which make it difficult for victim of crime to seek for remedies through existing tort provisions. It is the aim of this thesis to study on relationship between direct crime victim and profit from disclosure of wrongdoing fact and all form of action guidelines. The thesis does recommend that the adopted profit from crime law must provide clearly on what kinds of crimes or profit which victims was entitled. The applicability of victim s right in the profit from crime could be an effective solution for victims.